Lyapunov transformation and stability of differential equations in banach spaces - Tran, Thi Loan (Ukrains’kyi Matematychnyi Zhurnal, 1999)
A sufficient condition of exponential stability of regular linear systems with bifurcation on a Banach space is proved.